Mediating culture in the seventeenth-century German novel : Eberhard Werner Happel, 1647-1690 - Scholz Williams, Gerhild, 1942- (The University of Michigan Press, 2013)
"Eberhard Happel, Baroque German author of an extensive body of work of fiction and nonfiction, has for many years been categorized as a 'courtly-gallant' novelist. In Mediating Culture in the Seventeenth-Century German Novel, author Gerhild Scholz Williams argues that categorizing him thus is to seriously misread him and to miss out on a fascinating perspective on this dynamic period in German history. Happel primarily lived and worked in the vigorous port city of Hamburg, which was a 'media center' in terms of the access it offered to a wide library of books in public and private collections, and Hamburg's port status meant it buzzed with news and information. Happel's novels deal with many topics of current interest--explorations of national identity formation, gender and sexualities, Western European encounters with neighbors to the East, confrontations with non-European and non-Western powers and cultures--and they feature multiple media, including news reports, news collections, and travel writings. As a result, Happel's use of contemporary source material in his novels feeds the current interest in the impact of the production of knowledge on 17th-century narrative. Mediating Culture in the Seventeenth-Century German Novel explores the narrative wealth and multiversity of Happel's work, examines Happel's novels as illustrative of 17th-century novel writing in Germany, and investigates the synergistic relationship in Happel's writings between the booming print media industry and the evolution of the German novel"--